Demutualization of Securities Exchanges : A Regulatory Perspective - Elliott, Jennifer (IMF Working Papers; Working Paper, 2002)
Demutualization is a term used to describe the transition of a securities exchange from a mutual association of exchange members operating on a not-for-profit basis to a limited liability, for-profit company accountable to shareholders. Demutualization in its many forms has become a widespread phenomenon-one with increasing appeal in emerging market countries. Demutualization challenges the traditional approach to supervision of securities exchanges and raises issues regarding their role in the regulation and supervision of capital markets.